Study of Land Use Change from 1997 To 2014 Using Landsat Data In Bangli Regency - Naningsi, Nuranita; Osawa, Takahiro; Merit, I Nyoman (International Journal of Environment and Geosciences, 2018)
Bangli Regency is one of Regency in the Bali Province. The total area of  Bangli Regency is 52,081 hectares (9.24%) of total area of Bali Province (563,666 ha). The Growth and the development of the region Bangli Regency the positive impacts on the economy of the community, and the negative impacts on the environment. Land use change is one of the negative issue of development Bangli Regency. This study conduted the calculation of land use change from 1997 to 2014 using Landsat data in Bangli Regency. Landsat 5 TM, Landsat 7 ETM+ and Landsat 8 OLI/TIRS imageries were used to determine the land use map based, on using supervised classification method. The field data set the nine classes were classtuded based, on the classification were fresh water, bare land, forest, residential, bushes, irrigated paddy field, non irrigated paddy field, dry land and plantation. There results showed in land use changes from 1997 to 2014 that plantation increased (19,486.33 ha (36.89%)), and residential increased (1,872.00 ha (3.47%)), there is also a vast to reduction in dry land  (-10,868.90 ha (-21.21%)), forest (-6,333.34 ha (-12.24%)), irrigated paddy field (-1,619.50 ha (-3.17%)), bushes (-1,637.30 ha (-3.27%)), bare land (-63.00 ha (-0.17%)), non irrigated paddy field (-113.59 ha ( -0.26%)) and fresh water (-2.70 ha (-0.05%). The results accuracy rate was 89.45%. Anslyse of land use showed that the significant decrease of plantation area in Bangli Regency hill due to rapid development of infrastrusture of tourism and extensive residential area has increased particularly in sub district of the Kintamani District.